A new species of the genus Dendrolasiophilus Nomura, 2010 from the south of the Russian Far East (Coleoptera, Staphylinidae, Pselaphinae) - Kurbatov, Sergey A.; Kovalev, Alexey V. (Zootaxa, 2022)
Dendrolasiophilus subitus sp. nov. from the Russian Far East is described and illustrated. Some nomenclatural notes on the genus Dendrolasiophilus Nomura, 2010 are given.